2018
DOI: 10.1101/369439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstitution of a flexible SYCP3-DNA fibre suggests a mechanism for SYCP3 coating of the meiotic chromosome axis

Abstract: The synaptonemal complex (SC) keeps homologous chromosomes in close alignment during meiotic crossover. A hallmark of SC formation is the presence of its protein component SYCP3 on the chromosome axis. As SC assembly progresses, SYCP3 is deposited on both axes of the homologue pair, forming the lateral element (LE) in the tripartite structure of the mature SC. We have used cryo-electron tomography and atomic force microscopy to study the mechanism of assembly and DNA binding of the SYCP3 fibre. We find that th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Several recent studies have reported that in vitro, mammalian SYCP3 forms coiled-coil homotetramers that further assemble into large oligomeric structures with a 22 nm periodicity (Syrjänen et al, 2014). Further, SYCP3 can bind DNA through two short patches of basic residues near the N-terminus of this protein’s coiled-coil domain (Syrjänen et al, 2014), and large SYCP3 oligomers appear to bind and condense plasmid DNA (Bollschweiler et al, 2018). These data have led to a model whereby homotypic SYCP3 oligomers, interacting directly with DNA, form a major part of the mammalian chromosome axis (Syrjänen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported that in vitro, mammalian SYCP3 forms coiled-coil homotetramers that further assemble into large oligomeric structures with a 22 nm periodicity (Syrjänen et al, 2014). Further, SYCP3 can bind DNA through two short patches of basic residues near the N-terminus of this protein’s coiled-coil domain (Syrjänen et al, 2014), and large SYCP3 oligomers appear to bind and condense plasmid DNA (Bollschweiler et al, 2018). These data have led to a model whereby homotypic SYCP3 oligomers, interacting directly with DNA, form a major part of the mammalian chromosome axis (Syrjänen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported that in vitro, mammalian SYCP3 forms coiled-coil homotetramers that further assemble into large oligomeric structures with a 22 nm periodicity (49,51,52). Further, SYCP3 can bind DNA through two short patches of basic residues near the N-terminus of this protein's coiled-coil domain (49), and large SYCP3 oligomers appear to bind and condense plasmid DNA (52). These data have led to a model whereby homotypic SYCP3 oligomers, interacting directly with DNA, form a major part of the mammalian chromosome axis (49,52).…”
Section: Discussionmentioning
confidence: 99%
“…Further, SYCP3 can bind DNA through two short patches of basic residues near the N-terminus of this protein's coiled-coil domain (49), and large SYCP3 oligomers appear to bind and condense plasmid DNA (52). These data have led to a model whereby homotypic SYCP3 oligomers, interacting directly with DNA, form a major part of the mammalian chromosome axis (49,52). While we cannot rule out the formation of homotypic SYCP3 assemblies in meiotic cells, our data shows that the SYCP2:SYCP3 heterotetramer is more stable in solution than the SYCP3 homotetramer, and is therefore likely to be the preferred assembly in meiotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation